2017
DOI: 10.5296/ijssr.v5i1.11009
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Effect of Socio-Demographic Characteristics on Subjective Wellbeing

Abstract: The independent association between socio-demographic characteristics and subjective well-being is well studied, however, the moderating impact of those characteristics are yet to be established in literature. This study examines the moderating influence of socio-demographic characteristics on subjective well-being among residents in Ibadan metropolis. Using a descriptive survey design and a multistage sampling technique, 10 enumeration areas each were selected from the five major Local Government Areas (LGAs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 47 publications
1
3
1
1
Order By: Relevance
“…Although previous studies found several effects of age [30], gender [32] and education level [28], this current study did not show any significant effects on long-term SWB. Thus, other personal variables (e.g., personality, health, life changing events, home ownership and work situation) were found to be more important for explaining long-term SWB.…”
Section: Discussion and Future Researchcontrasting
confidence: 98%
See 2 more Smart Citations
“…Although previous studies found several effects of age [30], gender [32] and education level [28], this current study did not show any significant effects on long-term SWB. Thus, other personal variables (e.g., personality, health, life changing events, home ownership and work situation) were found to be more important for explaining long-term SWB.…”
Section: Discussion and Future Researchcontrasting
confidence: 98%
“…The importance of personality, in particular the personality traits extroversion and neuroticism, for explaining SWB was also confirmed by previous research [38,40,43]. Furthermore, the results on the relationship between work situation and long-term SWB suggests that retired people have more time to spend on positive activities that could contribute to their long-term SWB, which was also confirmed by previous research [29,30]. With regard to homeownership, similar results were found by Bloze & Skak [38].…”
Section: Discussion and Future Researchsupporting
confidence: 85%
See 1 more Smart Citation
“…The relationship between life satisfaction and various demographic factors has emerged in many studies. Income (Agrawal et al, 2011;Moller, 1996;Chow, 2005), education (Ross & van Willingen, 1997;Witter, Okun, Stock, & Haring, 1984), age (Lee & Browne, 2008;Mayungbo, 2017), gender (Diener, 1984;Inglehart, 2002), parental relationship (Çivitci, 2009;Erol & Kaba, 2018;Park, 2004;Sari & Ozkan, 2016;Shek, 1999;Young, Miller, Nortan, & Hill, 1995), perception towards parents' attitudes (Çivitçi, 2009), parents' socioeconomic status (Chu, Li, Li, & Han, 2015;Eryılmaz, 2010;Tuzgöl Dost, 2007), and religion (Doane, 2013;Green & Elliott, 2010) are examples of these socio-demographic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Yaş ile ilgili olarak çalışmalarda bütünlük söz konusu değildir. Her ne kadar bazı çalışmalar gençlerin yaşlılara göre daha mutlu olduğunu göstermiş olsa da (Mayungbo, 2017), yaş arttıkça memnuniyetin arttığını (Lee ve Browne, 2008) gösterenler de olmuştur. Diener' e (1984) göre kadınlar daha fazla olumsuz duygulanım rapor etseler bile daha fazla neşe, keyif deneyimledikleri için cinsiyet temelli farkların oldukça küçük olduğuna vurgu yapmaktadır.…”
Section: Yaşam Doyumu Ve Sosyo-demografik öZelliklerunclassified